2015
DOI: 10.1088/2041-8205/803/2/l17
|View full text |Cite
|
Sign up to set email alerts
|

Helioseismic Imaging of Fast Convective Flows Throughout the Near-Surface Shear Layer

Abstract: Using a new implementation of ring-diagram helioseismology, we ascertain the strength and spatial scale of convective flows throughout the near-surface shear layer. Our ring-diagram technique employs highly overlapped analysis regions and an efficient method of 3D inversion to measure convective motions with a resolution that ranges from 3 Mm at the surface to 80 Mm at the base of the layer. We find the rms horizontal flow speed to peak at 427 m s −1 at the photosphere and fall to a minimum of 124 m s −1 betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
96
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 29 publications
9
96
4
Order By: Relevance
“…Hathaway et al 2013), local time-distance helioseismology appears to indicate a gaping discrepancy between the Sun and current global simulations in that the latter produce significantly too much power at large scales (Hanasoge et al 2012). Local ring-diagram helioseismology, on the other hand, gives much larger convective velocities (Greer et al 2015). Nevertheless, at least circumstantial evidence suggests that a new paradigm of convection could be needed.…”
Section: Discussionmentioning
confidence: 85%
“…Hathaway et al 2013), local time-distance helioseismology appears to indicate a gaping discrepancy between the Sun and current global simulations in that the latter produce significantly too much power at large scales (Hanasoge et al 2012). Local ring-diagram helioseismology, on the other hand, gives much larger convective velocities (Greer et al 2015). Nevertheless, at least circumstantial evidence suggests that a new paradigm of convection could be needed.…”
Section: Discussionmentioning
confidence: 85%
“…Helioseismic observations by Hanasoge et al (2010Hanasoge et al ( , 2012 using the deep-focusing time-distance technique have not, however, detected large-scale convection velocities at the expected levels (Miesch et al 2012); see also Gizon & Birch (2012) for a comparison with both global simulations and radiation hydrodynamics simulations with realistic radiation and ionization physics included. Greer et al (2015) have suggested that the approach of Hanasoge et al (2012) may remove too much signal over the time span of the measurements. Using instead ring diagram analysis (Gizon & Birch 2005) with appropriately assembled averaging kernels to focus on the deeper layers, Greer et al (2015) instead find values of the turbulent rms velocities that are consistent with conventional wisdom.…”
Section: Introductionmentioning
confidence: 99%
“…Greer et al (2015) have suggested that the approach of Hanasoge et al (2012) may remove too much signal over the time span of the measurements. Using instead ring diagram analysis (Gizon & Birch 2005) with appropriately assembled averaging kernels to focus on the deeper layers, Greer et al (2015) instead find values of the turbulent rms velocities that are consistent with conventional wisdom. Moreover, they find that at large length scales corresponding to spherical harmonic degrees of 30 or below (corresponding to scales of about 140 Mm and larger), the rms velocity actually increases with depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, while the idea that supergranulation-scale flows may just be a manifestation of some form of thermal convection has a long history, it has often been dismissed due to the seeming lack of photometric intensity contrast at the same scales (Langfellner et al 2016). Besides, there is as yet no general consensus on local helioseismic estimates of the amplitude, depth and structure of subsurface flows on this scale (Nordlund et al 2009;Rieutord & Rincon 2010;Gizon et al 2010;Švanda et al 2013;DeGrave et al 2014;Švanda 2015) -or in fact on any scale larger than that (see, e.g., Hanasoge et al 2012;Gizon & Birch 2012;Hanasoge et al 2016;Greer et al 2015;Toomre & Thompson 2015;Greer et al 2016). Numerical simulations of the problem have, until recently, also been quite limited.…”
Section: Introductionmentioning
confidence: 99%